(untitled) (Journal of Digital System Development, 2024)
The advent of Industry 4.0 has fuelled the demand for Manufacturing Management Systems (MMS) in the manufacturing industry. This article presents the design and development of a comprehensive Product Sales Management System (PSMS) tailored for small and medium-sized manufacturing companies, focusing on the dairy product industry. Employing the Rapid Application Development (RAD) approach, the development process prioritised user-friendly interfaces and rapid prototyping. Through meticulous requirements gathering, key features were identified, including product information management, customer information management, sales order management, report generation, product advertisement management, and an analytic dashboard. Unified Modeling Language (UML) diagrams, such as use case, activity, and class diagrams, were utilised to visualise the system’s functionalities and ensure alignment with requirements. Iterative development and user feedback enhanced the system’s usability, resulting in a user-friendly interface for streamlined product sales handling. The proposed PSMS offers efficient management, enhanced communication, and revenue generation for manufacturing companies and tiny and medium-sized enterprises. Furthermore, the study contributes to an understanding of the system requirements and user interface of a PSMS, providing a valuable reference model for developers and researchers in the manufacturing industry. The proposed PSMS represents a significant step towards efficient product sales management, streamlining operations, and boosting manufacturers’ profitability. In future work, the PSMS’s user interface will be optimised for better mobile responsiveness, and its functionality will be extended to support collaborative sales management and provide manufacturers with advanced capabilities to enhance their sales processes and decision-making.